2022
DOI: 10.1038/s41556-022-00856-5
|View full text |Cite
|
Sign up to set email alerts
|

Leucyl-tRNA synthetase is a tumour suppressor in breast cancer and regulates codon-dependent translation dynamics

Abstract: Tumourigenesis and cancer progression require enhanced global protein translation 1 – 3 . Such enhanced translation is caused by oncogenic and tumour suppressive events that drive the synthesis and activity of translational machinery 4 , 5 . Here we report the surprising observation that leucyl-tRNA synthetase (LARS) becomes repressed during mammary cell transformation and in human breast cancer. Monoall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 59 publications
1
32
1
Order By: Relevance
“…Repression of LARS lead to impaired leucine codon-dependent translation of growth suppressive genes, including gammaglutamyltransferase 5 (GGT5) and epithelial membrane protein 3 (EMP3). which in turn enhances breast tumor formation and growth [32]. These results indicated that the function of LARS is complex, as it appears to have different functions in different tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Repression of LARS lead to impaired leucine codon-dependent translation of growth suppressive genes, including gammaglutamyltransferase 5 (GGT5) and epithelial membrane protein 3 (EMP3). which in turn enhances breast tumor formation and growth [32]. These results indicated that the function of LARS is complex, as it appears to have different functions in different tumors.…”
Section: Discussionmentioning
confidence: 89%
“…We hypothesized that one mechanism that could contribute to arginine tRNA repression may be reduced tRNA aminoacylation in the setting of arginine limitation. Reduced aminoacylation of certain tRNAs has been shown to destabilize tRNAs ( 21 ). To test this, we inhibited aminoacylation in CRC cells by depleting the arginyl-tRNA synthetase (RARS) and quantified tRNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…CD109, a known biomarker of brain tumors, was also elevated more in the PIK3CA E545K EVs than in their cells of origin [71]. Interestingly, leucine‐tRNA ligase (LARS), a tumor suppressor in breast cancers, was decreased in the EVs compared to their cells of origin [72]. Similarly, integrin beta‐4 (ITGB4), laminin subunit beta‐2 (LAMB2), and protein S100‐A14 (S100A14) were elevated in PIK3CA H1047R EVs more than in their cells of origin.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, leucine-tRNA ligase (LARS), a tumor suppressor in breast cancers, was decreased in the EVs compared to their cells of origin [72].…”
Section: Comparison With Cellular Proteomementioning
confidence: 99%